The Lipoxygenase Lox1 Is Involved in Light‐ and Injury-Response, Conidiation, and Volatile Organic Compound Biosynthesis in the Mycoparasitic Fungus Trichoderma atroviride - Speckbacher, Verena; Ruzsanyi, Veronika; Martinez-Medina, Ainhoa; Hinterdobler, Wolfgang; Doppler, Maria; Schreiner, Ulrike; Böhmdorfer, Stefan; Beccaccioli, Marzia; Schuhmacher, Rainer; Reverberi, Massimo; Schmoll, Monika; Zeilinger, Susanne (Frontiers in Microbiology, 2020)
The necrotrophic mycoparasite Trichoderma atroviride is a biological pest control agent frequently applied in agriculture for the protection of plants against fungal phytopathogens. One of the main secondary metabolites produced by this fungus is 6-pentyl-α-pyrone (6-PP). 6-PP is an organic compound with antifungal and plant growth-promoting activities, whose biosynthesis was previously proposed to involve a lipoxygenase. In this study, we investigated the role of the single lipoxygenase-encoding gene lox1 encoded in the T. atroviride genome by targeted gene deletion. We found that light inhibits 6-PP biosynthesis but lox1 is dispensable for 6-PP production as well as for the ability of T. atroviride to parasitize and antagonize host fungi. However, we found Lox1 to be involved in T. atroviride conidiation in darkness, in injury-response, in the production of several metabolites including oxylipins and volatile organic compounds, as well as in the induction of systemic resistance against the plant-pathogenic fungus Botrytis cinerea in Arabidopsis thaliana plants. Our findings give novel insights into the roles of a fungal Ile-group lipoxygenase and expand the understanding of a light-dependent role of these enzymes.